Wounded Woman : Healing the Father-Daughter Relationship - Leonard, Linda Schierse (Book collections on Project MUSE., 1982)
This book is an invaluable key to self-understanding. Using examples from her own life and the lives of her clients, as well as from dreams, fairy tales, myths, films, and literature, Linda Schierse Leonard, a Jungian analyst, exposes the wound of the spirit that both men and women of our culture bear-a wound that is grounded in a poor relationship between masculine and feminine principles. Leonard speculates that when a father is wounded in his own psychological development, he is not able to give his daughter the care and guidance she needs. Inheriting this wound, she may find th.